2007
DOI: 10.1038/sj.bjp.0706991
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitors of phosphodiesterase 5 (PDE 5) inhibit the nerve‐induced release of nitric oxide from the rabbit corpus cavernosum

Abstract: Background and purpose: Nitrergic neurons are important for erectile responses in the corpus cavernosum and impaired signalling results in erectile dysfunction, today treated successfully by oral administration of the selective phosphodiesterase 5 (PDE 5) inhibitors sildenafil, tadalafil and vardenafil. Although the importance of nitrergic neurons in urogenital function has become evident, it has not been investigated if the PDE 5 inhibitors affect the nerve-induced release of nitric oxide (NO). In a previous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 55 publications
3
11
0
Order By: Relevance
“…The concentrations at which alfuzosin exerted this enhancing effect were in the same range than its pKi value (8.2) determined in binding studies against α1‐adrenoceptors [42,43]. The relaxing effect of tadalafil on precontracted corpus cavernosum strips is in accordance with several studies, which previously investigated the relaxant properties of tadalafil in human [24] or in rabbit cavernosal strips [44,45]. Numerous studies have also previously evidenced that α1‐adrenoceptor antagonists could modulate corpus cavernosum contractile tone [31,46–48].…”
Section: Discussionsupporting
confidence: 79%
“…The concentrations at which alfuzosin exerted this enhancing effect were in the same range than its pKi value (8.2) determined in binding studies against α1‐adrenoceptors [42,43]. The relaxing effect of tadalafil on precontracted corpus cavernosum strips is in accordance with several studies, which previously investigated the relaxant properties of tadalafil in human [24] or in rabbit cavernosal strips [44,45]. Numerous studies have also previously evidenced that α1‐adrenoceptor antagonists could modulate corpus cavernosum contractile tone [31,46–48].…”
Section: Discussionsupporting
confidence: 79%
“…[7][8][9][10] Some drugs such as inhibitors of PDE 5 or other vasodilators, which can promote the relaxation of corpus cavernosum smooth muscle, can be potentially used to treat ED. [11][12][13][14][15][16][17][18][19] It has been shown that there are many Chinese traditional herbals that can enhance sexual activity. [20][21][22][23][24] Recently, there is an increasing interest in investigating their effective components.…”
Section: Introductionmentioning
confidence: 99%
“…These findings are supported by data on the IC 50 values of these drugs in previous studies using isolated smooth muscle. [1314]…”
Section: Discussionmentioning
confidence: 99%